Evidence that class size matters in 4th grade mathematics: An analysis of TIMSS 2007 data for Colombia (2014)
Like students in most developing countries, Colombian students in 4th grade performed poorly in the TIMSS 2007 test of mathematics skills, achieving an average score of 355 relative to an internationalmean of 500. After controlling for other factors and misreporting error, I find that large classes have substantial adverse effects on student achievement. Increases in class size from 20 to 53 students reduce test scores by about 80 points, or 2.4 points for each additional student in the class. Most likely this is the cumulative effect of class size in grades one to four on achievement in 4th grade.